2022
DOI: 10.1002/ijc.34260
|View full text |Cite
|
Sign up to set email alerts
|

Time intervals in the care pathway to cancer diagnosis during the COVID‐19 pandemic: A large retrospective study from a high‐volume center

Abstract: Despite extensive research on cancer care during the COVID‐19 pandemic, evidence on the impact on prediagnostic time intervals is lacking. To better understand how COVID‐19 changed the pathway to diagnosis of cancer, we examined the length of intervals from symptom onset to diagnosis for 13 common cancer types with known clinical stage over 1‐year nonpandemic period (March 2019 to March 2020; N = 844) and three biannual COVID periods (March 2020 to September 2021; N = 1172). We analyzed the patient interval (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The COVID-19 pandemic has been shown to negatively affect referral rates to specialty services for a variety of medical and surgical conditions 26–29 . We believe our study is the first to investigate the impact of COVID-19 on PCP referral rates to specialty providers for UI.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The COVID-19 pandemic has been shown to negatively affect referral rates to specialty services for a variety of medical and surgical conditions 26–29 . We believe our study is the first to investigate the impact of COVID-19 on PCP referral rates to specialty providers for UI.…”
Section: Discussionmentioning
confidence: 90%
“…The COVID-19 pandemic has been shown to negatively affect referral rates to specialty services for a variety of medical and surgical conditions. [26][27][28][29] We believe our study is the first to investigate the impact of COVID-19 on PCP referral rates to specialty providers for UI. Although we found no significant reduction in the diagnosis of UI during the pandemic, there was a statistically significant decrease in referrals to specialist physicians.…”
Section: Discussionmentioning
confidence: 96%
“…A second evaluation from a large retrospective study from a high-volume centre demonstrated that between the prepandemic period and March 2020 to March 2021, differences in the clinical stage between periods were relevant, with cancers from the mid-period (September 2020 to March 2021) showing the most advanced stage. A shift to a later stage was plausibly a result of delayed intervals in the early COVID period [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This increase in time, whether due to COVID-related precautions or the load of COVID patients itself, led to delayed surgeries in many countries because of a restricted number of beds available and overburdened clinicians. The increase in lag time to a cancer diagnosis resulted in more advanced tumor stages at presentation during the late-pandemic period compared to the prepandemic period [5][6][7][8]. Delays in cancer diagnosis were associated with expected increased deaths, up to five years after diagnosis, as reported by a UK population-based modelling study [6].…”
Section: Introductionmentioning
confidence: 99%